MENGABDI TANPA MENGORBANKAN: UPAYA MEMBANGUN KESEIMBANGAN IDEAL PELAYANAN PASTORAL DAN KELUARGA (MINISTRY-FAMILY BALANCE) BAGI PENDETA - Edu, Ferdinand (Diegesis : Jurnal Teologi, 2025)
This study examines the role conflict experienced by pastors in balancing pastoral ministry and family responsibilities. As spiritual leaders, pastors face significant expectations from the congregation while also being responsible for maintaining harmony within their families. The imbalance between these roles often leads to mental health challenges, weakened family relationships, and reduced effectiveness in ministry. Using a qualitative descriptive approach, this study analyzes the theological and ethical foundations of pastoral leadership and family obligations through a literature review. The findings highlight that role conflict in pastoral ministry stems from excessive workload, unrealistic expectations, and lack of clear boundaries between church and family life. To achieve an ideal balance, pastors must adopt ministry-family integration, time management, and transparent communication. Additionally, prioritizing both ministry and family as a form of devotion to God ensures a holistic and sustainable pastoral service. The study concludes that achieving balance is essential for pastoral effectiveness and family well-being, requiring intentional strategies to prevent burnout and relational discord.